First record of Polycotylidae (Sauropterygia, plesiosauria) from the Upper Cretaceous of Antarctica - Novas, Fernando Emilio; D'angelo, Julia Soledad; O'gorman, Jose Patricio; Agnolin, Federico; Lirio, Juan Manuel; Isasi, Marcelo Pablo (Cretaceous Research)
In the present paper we report the incomplete skeleton of an indeterminate polycotylid that includes the articulated pelvic girdle. The material was collected from the Alpha Member of the Santa Marta Formation (upper Coniacian-lower Campanian) on James Ross Island, Antarctic Peninsula. The specimen is referred to the Polycotylidae on the basis of its very elongate ischia and rimmed anterior and posterior articular surfaces of the dorsal vertebrae. Additionally, the caudal vertebrae show confluent parapophyses and neural arch facets. The present report constitutes the first record for polycotylids in Antarctica, being an important addition to the fossil marine reptile diversity. Polycotylids are a scarce component of the Weddellian herpetofauna, which are dominated by aristonectine and non-aristonectine elasmosaurids. In contrast, in Northern Hemisphere assemblages, polycotylids are an important component of the plesiosaur diversity. The scarcity of polycotylids may constitute another distinctive feature of Weddellian plesiosaur faunas. Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: D'angelo, Julia Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Agnolin, Federico. Universidad Maimónides; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Fundación de Historia ...